Cytokine production by the bioptates of invasive non-specific breast carcinoma as a criterion for the use of acetylamide form of synthetic HLDF-6 peptide for differentiation therapy of breast cancer - E. D. Mangazeeva; A. A. Studenikina; E. S. Michailova; D. V. Morozov; S. L. Ryzhikova; Yu. G. Druzhinina; A. V. Proskura; A. P. Bogachuk; V. M. Lipkin; A. I. Autenshlyus (Медицинская иммунология)
Differentiation therapy is a promising direction in treatment of oncological diseases. It is based on usage of agents that increase the degree of tumour cell differentiation, and thereby reduce the malignant potential of the neoplasm. Such effects are shown for the acetyl-amide form of the synthetic peptide HLDF-6. The peptide was previously found to reduce the relative content of low-differentiated cells in breast cancer biopsy specimens. However, the mechanisms of the peptide's effect on tumour cells and its microenvironment remain unknown. The effect of this peptide may be associated with altered functional activity of the tumour. The aim of our study was to investigate the effect of acetyl-amide form of synthetic HLDF-6 peptide on cytokine production by bioptates of invasive non-specific breast carcinoma. Morphometric analysis of bioptates obtained from 40 women with invasive breast carcinoma of nonspecific type before and after exposure to acetyl-amide form of synthetic peptide HLDF-6 was performed. To evaluate the effect of this peptide, we proposed an estimated index for HLDF-6 effect being expressed in conventional units (c. u.). The index of HLDF-6 influence of 0.9 с. u. and less is accepted as a significant effect. Depending on the index value, the patients were divided into two groups. The first group consisted of 27 patients with a significant effect of the studied peptide, the second group consisted of 13 patients without a significant effect. Concentrations of TNFa, IFNg, VEGF, G-CSF, GM-CSF, MCP-1, IL-6, IL-8, IL-10, IL-17, IL-18 and IL-1b were determined in parallel in supernatants of bioptates before and after incubation with the studied peptide using the enzyme immunoassay technique. The influence (effect) index, IE-HLDF-6-cytokine, expressed in conventional units (c. u.), reflected the effect of the acetyl-amide form of the synthetic HLDF-6 peptide on cytokine production by tumour bioptates. The study showed that spontaneous production of GM-CSF in the first group was significantly lower than in the second group. However, the concentration of this cytokine under the influence of HLDF-6 peptide significantly increases in group I in comparison with group II, as evidenced by statistically significant difference in IEHLDF-6-cytokine. According to the results of ROC-analysis, a good model quality was obtained in the study of IE-HLDF-6-GM-CSF and relative content of low-differentiated cells, which may serve as a basis for using this index as a cut-off point used for selection of patients who may be candidates for differentiation therapy with acetyl-amide form of synthetic peptide HLDF-6.